2019
DOI: 10.31413/nativa.v7i4.6683
|View full text |Cite
|
Sign up to set email alerts
|

Produtividade De Diferentes Genótipos De Amendoim Submetidos a Diferentes Formas De Adubação

Abstract: O amendoim possui grande importância para os pequenos agricultores do Nordeste brasileiro, contudo apresenta baixa produção nesta região. Neste sentido, técnicas que aumentem a produção dessa cultura são importantes. Objetivou-se nesse trabalho avaliar a ação de diferentes formas de adubação sob os componentes de produção de quatro genótipos de amendoim. O experimento foi conduzido na Universidade da Integração Internacional da Lusofonia Afro-Brasileira (UNILAB), Redenção, Ceará. O delineamento usado foi intei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 13 publications
0
2
0
5
Order By: Relevance
“…Results of studies using organic sources for the fruit length variable were reported by Sales et al (2019), in which the use of bovine BF exceeded the other treatments in the results of this variable. However, Souza et al (2019) noticed that the vegetable ash used as fertilizer showed superior performance, for pod length, in the four studied peanut genotypes.…”
Section: Adubação Mineral (Am); Biofertilizante Bovino (Bf); Cinza Ve...mentioning
confidence: 87%
See 2 more Smart Citations
“…Results of studies using organic sources for the fruit length variable were reported by Sales et al (2019), in which the use of bovine BF exceeded the other treatments in the results of this variable. However, Souza et al (2019) noticed that the vegetable ash used as fertilizer showed superior performance, for pod length, in the four studied peanut genotypes.…”
Section: Adubação Mineral (Am); Biofertilizante Bovino (Bf); Cinza Ve...mentioning
confidence: 87%
“…Among the practices, the following highlighted: irrigation management, phytosanitary control, soil correction, and fertilization. Crop nutrition through the use of correctives and fertilizers has a direct influence on productivity and food quality (SOUZA et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contudo, é dependente do manejo adequado, monitoramento prévio da fertilidade do solo e do acompanhamento do estado nutricional da lavoura para assegurar o êxito da produção agrícola (BOARETTO; NATALE, 2016). Não obstante, a interação entre nutrição de plantas e salinidade ainda é muito complexa, devido à fonte, o tipo de adubo químico, orgânico ou organomineral a ser aplicado (SOUZA et al, 2019;SILVA et al, 2022).…”
Section: Introductionunclassified
“…Arachis hypogea L. (Figura 1), gênero Arachis, é conhecida popularmente por "amendoim". É uma espécie inserida entre as dicotiledôneas, herbáceas e anuais, pertencente à família Fabaceae, assim como o feijão e a soja, sendo Arachis uma das principais culturas oleaginosas de âmbito nacional e internacional (Sousa et al, 2014;Lisboa et al, 2019;Souza et al, 2019). Segundo o Registro Nacional de Cultivares, existem atualmente, vinte e seis cultivares registradas da espécie A. hypogaea, que se destinam prioritariamente, à comercialização de sementes no país.…”
Section: Introductionunclassified